Cognitive Behaviour Group Counseling with Cognitive Restructuring and Self-Instruction Techniques to Reduce The Social Anxiety of Public Senior High School 3 Pati - Kurniawan, Edi; Japar, Muhammad; Sutoyo, Anwar (Jurnal Bimbingan Konseling)
This study aimed to examine the effectiveness of cognitive behavior therapy group counseling with cognitive restructuring and self-instruction techniques to reduce the social anxiety of Public Senior High School 3 Pati. The study used an experimental method with the design of randomized pre-test ? post-test comparison group. Meanwhile, there were 24 students of Public Senior High School 3 Pati who experienced social anxiety involved as the subjects of the study. They were divided into three groups, namely group counseling with cognitive restructuring technique, group counseling with self-instruction technique, and group counseling with the combination of cognitive restructuring and self-instruction techniques. The results showed that cognitive restructuring and self-instruction techniques were able to reduce social anxiety. The combination of both techniques performed more effective in reducing social anxiety than the partial use, namely cognitive restructuring or self-instruction only. Further, this study for counselors implies that they are suggested to use cognitive behavior therapy group counseling with cognitive restructuring and self-instruction techniques to reduce social anxiety of students. Moreover, the implication of the counseling is discussed in the results and discussion chapter.